A neglected predictor of environmental damage: The ecological paw print and carbon emissions of food consumption by companion dogs and cats in China. (1st September 2018) - Su, Bingtao; Martens, Pim; Enders-Slegers, Marie-José
Abstract: Food consumption has considerable impacts on the environment. Recently, increasing numbers of companion animal owners feed their animals with high nutritional food, which requires much land space and has great impacts on carbon emissions. Therefore, the environmental impacts of food consumption by companion animals can be significant, especially in a country with a large companion animal population, like China. In the present study, the ecological indicators of the ecological paw print (EPP), carbon emission and energy consumption have been introduced for the first time to quantify the environmental impacts of food consumption by companion dogs and cats in China. Our results showed that the dietary EPP and carbon emissions of an average-sized dog relying on commercial dry food (0.82–4.20 ha year −1 and 0.037–0.190 ton. year −1 ) were ca. eight and three times higher than those of the dog relying on human leftover food (0.11–0.53 ha year −1 and 0.014–0.064 ton. year −1 ). There were more than 27.4 million companion dogs and 58.1 million companion cats in China in 2015. Assuming all these dogs and cats eat commercial dry food, the dietary EPP of the total dogs and cats was 43.6–151.9 million ha. year −1, which was equivalent to the dietary ecological footprint (EF) of 5.1%–17.8% (70.3–245.0 million) of Chinese people in 2015. The annual food consumption of all these dogs and cats was responsible for up to 2.4–7.5 million tons carbon emissions, which was equivalent to the entire carbon emissions of 2.5%–7.8% (34.3–107.1 million) of Chinese people in terms of food consumption in 2015. Our results also demonstrated that some companion animals (especially large dogs) consumed more food energy than their actual needs to keep normal activity, which resulted in food waste and exacerbated the environmental burden. This research develops an accurate method for companion animals' dietary EPP calculation and quantifies the significant environmental impacts by investigating their dietary carbon emissions and energy consumptions. Findings from this study will motivate companion animal owners to reconsider the feeding regimens and husbandry activities, improve owners and even the whole Chinese people's awareness of sustainability, and ultimately promote the whole country's sustainable development. Highlights: We first quantified the dietary "ecological paw print" of pet dogs and cats in China. We first quantified the carbon emissions and energy requirement of these animals. The dietary EPP of two large dogs is equivalent to 20 Chinese people's dietary EF. The dietary EPP of all pet dogs and cats in China was 43.6–151.9 million ha. year −1 . The carbon emissions of all these animals in China were 2.4–7.5 million tons. year −1 .